Strategi Branding Melalui Inovasi Produk Dan Pemasaran Digital Pada UMKM Emak Farm Dan Hidroponik - Agata Winda Christianti; Halawatul Ulum (Jurnal Manajemen Kreatif dan Inovasi, 2024)
Emak Farm and Hydroponics is one of the business branches of the East Java Al-Muslim Foundation headed by Drs. Masyhuda. In 2018, Mr. Artha was entrusted to run the Emak Farm and Hidroponic business by Drs. Masyhuda. In his pioneering journey, Pak Artha met Pak Kenta (Head of Surabaya Vegetable Garden). He collaborated with Surabaya Vegetable Garden as a vegetable supplier before finally deciding to go door to door to customers in the Pondok Chand area. The purpose of establishing the Emak Farm and Hidroponic business is to become a useful garden, become a role model and always learn new science or new innovations about hydroponics. In the process of realizing useful gardens, Emak Farm and Hidroponic assisted the Farmer Groups (Poktan) in helping sales and making markets for the groups. The challenge faced by Emak Farm and Hidroponic today is to increase understanding for groups in terms of packaging and shipping to customers who conform to the standard. Another thing that is a challenge as well as motivation for Emak Farm and Hidroponic is in terms of science in hydroponic farming which continues to develop. In this study, researchers intend to review innovative benefit-oriented marketing strategies carried out by UMKM, Emak Farm and Hydroponics.